TEACHERS' PROFESSIONALISM IN IMPLEMENTING SOCIAL CULTURE AND RELIGIOUS VALUES AT SDN 16 TERNATE CITY: PROFESIONALISME GURU DALAM MENGIMPLEMENTASIKAN BUDAYA SOSIAL DAN NILAI-NILAI RELEGIUS DI SDN 16 KOTA TERNATE - Lily Saleh; Jusan Yusuf; Mohtar Kamisi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Instilling social culture and religious values from an early age is an important part of character building for students. Teachers as agents of change have a strategic role in implementing these values in the school environment. This study aims to describe teacher professionalism in implementing social culture and religious values at SDN 16 Kota Ternate. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers at SDN 16 Kota Ternate have demonstrated good professionalism through the integration of social and religious values in the learning process, exemplary attitudes and behaviors, and the habituation of religious and social activities in the school environment. The obstacles faced include the lack of supporting facilities and the still existing differences in student backgrounds, but can be overcome with a personal and collaborative approach. In conclusion, teacher professionalism has a significant contribution in instilling social culture and religious values, which have a positive impact on the formation of student character.